PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELJARAN GEOGRAFI KELAS X DI SMAN 1 GALESONG SELATAN KABUPATEN TAKALAR - Wahyuni, Qoriatul (UNIVERSITAS NEGERI MAKASSAR, 2018)
The research is Classroom Action Research Which aims to Increase Student Learning Achievement On subjects Geography Student ClassX In senior high school class X Galesong selatan Semester 2 of school year 2016/2017, as 33 students consist of 7 male students and 26 female students. This research was conducted in two cycles carried out during six meetings. Each cycle comes from the four stages of planning, that is execution, observation / evaluation and reflection. This type of research is a description. Technique of data collection is done by using the data of the study result and observation student activity. Analyzed by using quantitative and qualitative analysis. Minimum grade criteria class X PIS senior high chool Galesong Selatan is 75 for subjects Geography (1) On the basis of quantitative analysis,the result of the learning cicle I 42 percent of completenes l and second cycle with the percentage increase was 87.05 percent (2) Qualitatively, there was a change in the activity of students' geography learning in cycle I 66.7 percent experienced a change in attitude in cycle II 87.05 percent included in the active category . Based on the results of the analysis and discussion it was concluded that the application of Problem Based Learning can improve students' geography learning achievement in senior high school Galesong SelatanÂ